Xper-CT combined with laser-assisted navigation radiofrequency thermocoagulation in the treatment of trigeminal neuralgia - Xiong, Fengzhen; Zhang, Tao; Wang, Qingbo; Li, Chenglong; Geng, Xin; Wei, Qi; Yuan, Zhengbo; Li, Zefu (Frontiers in Neurology, 2022)
Abstract Objective: Our objective was to study the clinical feasibility of Xper-CT combined with laser-assisted radiofrequency thermocoagulation in the treatment of trigeminal neuralgia. Material and methods: A retrospective analysis was made of 60 patients with trigeminal neuralgia who visited the Affiliated Hospital of Binzhou Medical University from January 2019 to May 2021. According to the different surgical methods, we were divided into C-arm X-ray group and laser navigation group. The operation time, operative complications, postoperative 24 hours, postoperative 3 months and 6 months Barrow Neurotics Institute (BNI) score were recorded and compared. Results： Compared with the C-arm X-ray-guided puncture group, Xper-CT combined with laser-assisted navigation has the obvious advantages of shorter total puncture time, shorter surgical time, higher success rate of first puncture, and better surgical effect. Conclusion: Radiofrequency therapy of trigeminal neuralgia with Xper-CT combined with laser-assisted navigation has a good clinical effect and can be promoted and applied.